Pemeriksaan Kondisi Jembatan Wai Welinaha I Negeri Hatu Kecamatan Leihitu Barat Maluku Tengah dengan Menggunakan Metode BMS dan BCR: Inspection of the Condition of the Wai Welinaha I Negeri Hatu Bridge, West Leihitu Sub-District, Central Maluku Using the BMS and BCR Method - Tasijawa, Sulfa Ima; Roberth, Herry Henry; Tuanakotta, Abraham (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Bridges are one of the important infrastructures in transportation that have a vital role in connecting one place to another. Bridges are also one of the important elements in the development of a country because they can support economic growth and community welfare. However, in the management and maintenance of bridges, there are often various challenges faced, such as structural wear problems, declining material strength, and damage due to natural factors such as earthquakes and floods. The Bridge Management System (BMS) and Bridge Condition Rating (BCR) methods are used in this study to identify and provide an assessment of the bridge condition value, the results of the bridge assessment will be used to determine the maintenance procedures that can be carried out on the bridge. From the results of the inspection in the field, there were several damages such as damaged or missing components, changes in the shape of components, concrete loss, accumulated garbage, cracks and rough or perforated surfaces in the surface layer, cracks in the bridge expansion joints, as well as a decrease in paint and glavanis. From the results of the examination and assessment using two methods. The BMS method is known to have the general condition value of the Wai Welinaha I bridge with a condition value of 0 or in a state (Good), and the damage codes on the Wai Welinaha I bridge are 806, 204, 204, 202, and 202. In the BCR method, the proposed inspection of the Wai Welinaha I bridge is routine and periodic maintenance. From the results of the current review that has been carried out, it can be concluded that the level of damage to the bridge has increased. With some areas damaged.